10 Clinical outcomes and programming strategies of implantable cardioverter defibrillator (ICD) devices during childhood in hypertrophic cardiomyopathy: a UK national cohort study. (17th July 2020) - Norrish, Gabrielle
Abstract : Introduction: Sudden cardiac death (SCD) is the most common cause of mortality in childhood hypertrophic cardiomyopathy (HCM). ICDs have been shown to be effective at terminating malignant ventricular arrhythmias but at the expense of a high incidence of complications. The optimal device and programming strategies to reduce complications in this patient group is unknown. To describe the programming strategies and clinical outcomes of ICD implantation in childhood HCM. Methods: Anonymised, non-invasive clinical data were collected from a retrospective, longitudinal multi-centre cohort of children (<16 years) with HCM (n=687) and an ICD in-situ from the United Kingdom. Results: 96 patients (61 male (64%), 6 non-sarcomeric (6%)) underwent ICD implantation at a median age 14yr (IQR 11-16, range 3-16) and weight 52.3 Kg (IQR 34.8-63.1). Indication for ICD was primary prevention in 72 (75%) and secondary 24 (25%). 82 (85%) had an endovascular system, 3 (3%) epicardial and 11 (12%) subcutaneous system. For those with an endovascular system, 14 (15%) had a dual-coil shock lead and 48 (50%) an atrial lead. 61 patients (74%) were receiving one or more cardioactive medications at implantation [B blockers n=56, 70%, disopyramide n=14, 15%, amiodarone n=7, 7%, calcium channel blocker n=7, 9%, other n=5, 6%]. Programming practices varied; all had VF therapies activated (median 220bpm, IQR 212-230), 70 (73%) had a VT zone programmed (median rate 187 bpm, SD 20.9) of which 26 (27%) had therapies activated. 50 patients (61%) had antitachycardia pacing (ATP) activated. Over a median follow up of 53.6 months (IQR 27.3, 108.4) 4 patients (4.2%) following arrhythmic events. 25 patients had 53 appropriate therapies (ICD shock n=47, ATP n=8), incidence rate 5.22 (95% CI 3.5-7.8). On univariable analysis, secondary prevention indication for ICD implantation was the only predictor of therapy [16 (64%) vs 8 (11.3%), p value <0.001]. 8 (8.3%) patients had 9 inappropriate therapies (ICD shock n=4, ATP n=5), incidence rate 1.37 (95% CI 0.65-2.8) caused by T wave oversensing (n=2, lead migration (n=1), supraventricular tachycardia (n=1). Device complications were seen in 30 patients (31%); lead complications n=16, infection n=10, other n=5. No clinical characteristics predicted time to inappropriate therapy or lead complication. Conclusions: In a contemporary cohort of children with HCM, the incidence of inappropriate therapies is lower than previously reported, yet complication rates remain higher than reported in adult patients. No clinical, device or programming strategies were associated with inappropriate therapies or lead complications. Conflict of Interest: Nil